PTH-327 Epithelial misplacement versus polyp cancer: shedding new light on the diagnostic conundrum. (22nd June 2015) - Griggs, R; Nallala, J; Lloyd, G; Cook, T; Kendall, C; Barr, H; Stone, N; Shepherd, N
Abstract : Introduction: Colorectal cancer is the second most common cause of cancer death in the UK. 1 Colonic adenomas are often removed during colonoscopy as part of the Bowel Cancer Screening Programme to identify early cancers and improve patient survival rates. 2 Sigmoid adenomas may show features of benign epithelial misplacement in the submucosal stalk which in some cases may resemble an early infiltrating adenocarcinoma or polyp cancer 3 causing substantial diagnostic conundrum for pathologists. The aim of this study was to investigate and demonstrate the use of novel high resolution infrared spectroscopy to differentiate colonic epithelial misplacement (EM) from polyp cancer. Method: 28 cases in total for the EM and cancer pathology groups were identified from 2011–2014. Tissue samples were formalin fixed and paraffin embedded, routinely processed and thin sections mounted onto calcium fluoride slides. Rapid mapping using a novel high resolution infrared spectrometer with a spatial resolution of 1.1 microns was performed on the tissue sections and the absorption spectra measured for each case. Accepted methods of multivariate spectral analysis were undertaken to elucidate the differences between the two pathologies across the dataset and classify the tissue based on the spectra. Results: High resolution infrared spectral imaging was successfully performed on the colonic tissue. Analysis of 28 cases in two pathology groups generated over 500, 000 spectra representative of the molecular biology of EM and cancer cases. Spectral differences between the two groups were analysed using principal component and linear discriminant analysis and a classification model built. Leave one sample out cross validation (LOSOCV) resulted in a sensitivity of 74.6% and a specificity of 82.3% for the technique to successfully discriminate EM from cancer. Conclusion: Analysis of spectral data generated from novel high resolution infrared spectral imaging of colonic tissue has been proven to be successful in differentiating EM from cancer cases. The diagnostic difficultly of differentiating these cases is well documented, especially as one disease state approaches that of the other. However, novel high resolution spectroscopy may offer a new tool to aid the accurate diagnosis of early cancers. This technique has the potential to be used as an automated adjunct to traditional pathological diagnostics, may increase diagnostic speed in difficult cases and improve the efficiency of the patient management pathway. Disclosure of interest: None Declared. References: www.cancerresearchuk.org Mandel JS, Church TR, Bond JH, et al . N Engl J Med. 2000;343:1603–1607 Muto T, Bussey HRJ, Morson BC. J Clin Pathol. 1973;26 :25–31